2010
DOI: 10.1089/jwh.2008.1094
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Reproductive and Breast Cancers among Older Lesbians

Abstract: These findings suggest that older lesbians may have greater risk factors for some, not all, reproductive cancers when compared with their heterosexual sisters, specifically, increased risk for breast, ovarian, and endometrial cancer but decreased risk for cervical cancer. Further research should be done to determine if these risks translate into actual disease for lesbians as well as culturally appropriate ways to modify the risks among lesbians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 16 publications
0
47
0
1
Order By: Relevance
“…1 This report outlined in detail the unique concentration of common breast cancer risk factors among lesbian and bisexual women resulting from differences in reproductive behaviors, lifestyle factors, and use of routine preventive screening methods. Since that time, additional studies [4][5][6][8][9][10][11][12][13][14][15]21,27 have provided further support for these concerns. However, whether this concentrated pattern of breast cancer risk factors causes detectably higher rates of incident breast cancer for women with minority sexual orientation is unclear at this juncture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This report outlined in detail the unique concentration of common breast cancer risk factors among lesbian and bisexual women resulting from differences in reproductive behaviors, lifestyle factors, and use of routine preventive screening methods. Since that time, additional studies [4][5][6][8][9][10][11][12][13][14][15]21,27 have provided further support for these concerns. However, whether this concentrated pattern of breast cancer risk factors causes detectably higher rates of incident breast cancer for women with minority sexual orientation is unclear at this juncture.…”
Section: Discussionmentioning
confidence: 99%
“…3 One dimension is reproduction related, where sexual minority women experience higher rates of nulliparity, lower rates of abortion, fewer pregnancies, lower rates of breastfeeding, and older age at first childbirth compared to heterosexual women. [4][5][6] A second dimension involves behavioral risk factors. Here, it has been observed that sexual minority women report more frequent alcohol consumption and tobacco use and higher rates of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study found no difference in C-reactive protein, a marker for CVD, in young adult sexual minority compared with heterosexual women (Hatzenbuehler et al, 2013). Few of these studies reported cancer prevalence; one found no difference between older lesbians and their heterosexual sisters for breast cancer (Zaritsky & Dibble, 2010). These findings are also supported by another recent review of the literature of chronic physical health problems in sexual minority women (Eliason, 2014b), which found that, of 10 studies that reported diabetes, none found elevated rates among sexual minority women; and of 12 studies that reported hypertension, three found heterosexual women to have higher rates and none found higher prevalence among sexual minority women.…”
Section: Obesity Paradoxmentioning
confidence: 99%
“…Another national study included more than 30,000 college students, and most of the 123 participating campuses used random sampling procedures (Struble, Lindley, Montgomery, Hardin, & Burcin, 2010). Eight were national samples, mostly using online surveys Brittain, Dinger, & Hutchinson, 2013;Davids & Green, 2011;Fredriksen-Goldsen et al, 2012a;Jun et al, 2012;McElroy & Jordan, 2014;Struble et al, 2010;Zaritsky & Dibble, 2010 Found that sexual orientation weight discrepancies began in adolescence. L marginally heavier than H; B and mostly H significantly heavier than completely H Did not report BMI means or frequency, but did report relative risk (RR) using heterosexual as referent: Overweight:…”
mentioning
confidence: 99%